THE EFFECTIVENESS OF EDUCATION TO IMPROVE KNOWLEDGE AND ATTITUDES ON STUNTING PREVENTION IN MOTHERS WHO HAVE UNDER-CHILDREN A: LITERATURE REVIEW - Reni Anggraeni; , Tukimin Bin Sansuwito; Nisha Nambiar (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Accelerating the reduction of stunting in toddlers is a priority program of the Government. Educational efforts for mothers with toddlers and promotion of stunting health include nutrition/nutrition education for toddlers, children, and the whole family and clean and healthy living behaviours that must be carried out by families and all members of the community in order to create a healthy environment for children to live in. Purpose: To examine and synthesize research evidence on the effectiveness of education to increase knowledge and attitudes towards stunting prevention in mothers with toddlers. Methods: Protocol and evaluation from the literature review using the PRISMA checklist. A literature search was conducted from June to September 2022. The literature search used four databases with high and medium-quality criteria, namely Pubmed, Scient Direct, Scopus, and garuda portal, with 414 articles found. From the election results, the number of articles discussed was 16 articles. Results: The results found 16 articles that discussed stunting education, where changes in stunting prevention knowledge were visible for the better. The results obtained from the discovery of 16 articles that discussed stunting prevention education resulted in a positive change in attitude toward stunting prevention. Conclusion: The results of changes in stunting prevention knowledge seem to improve, and stunting prevention education is positive. Where the results of changes in stunting prevention knowledge change are visible for the better. The results obtained from the discovery of 16 articles that discussed stunting prevention education resulted in a positive change in attitude toward stunting prevention. Conclusion: The results of changes in stunting prevention knowledge seem to improve, and stunting prevention education is positive. Where the results of changes in stunting prevention knowledge change are visible for the better. The results obtained from the discovery of 16 articles that discussed stunting prevention education resulted in a positive change in attitude toward stunting prevention. Conclusion: The results of changes in stunting prevention knowledge seem to improve, and stunting prevention education is positive.